PROPERTY RIGHTS FOR NATURAL RESOURCES MANAGEMENT IN INDONESIA: HAVE THEY BEEN RULED UNCONSTITUTIONAL? - Waddell, Sarah (UI Scholars Hub, 2012)
A new property right known as the coastal waters commercial use right (Hak Pengusahaan Pengairan Pesisir (HP-3)) introduced by Law No. 27 of 2007 regarding the Management of Coastal and Small Island Areas has been ruled inoperative by the Constitutional Court. The decision raises a question as to whether the door has been closed to marketbased instruments that rely on property rights as a policy tool in natural resources management. This concern is relevant as legal developments in natural resources law internationally have moved away from traditional forms of regulation to focus on the creation of new statutory property rights such as fisheries rights, water use rights and rights associated with carbon sequestration. An exploration of theConstitutional Court’s decisionsuggests that a similar line of reasoning would not, and should not,arise in relation to other forms of property rights that the Government of Indonesia may seek to introduce in the future.